Lipocalin-2 is increased in progressive multiple sclerosis and inhibits remyelination - Al Nimer, Faiez (Neurol Neuroimmunol Neuroinflamm, 2016)
OBJECTIVE: We aimed to examine the regulation of lipocalin-2 (LCN2) in multiple sclerosis (MS) and its potential functional relevance with regard to myelination and neurodegeneration. METHODS: We determined LCN2 levels in 3 different studies: (1) in CSF and plasma from a case-control study comparing patients with MS (n = 147) with controls (n = 50) and patients with relapsing-remitting MS (n = 75) with patients with progressive MS (n = 72); (2) in CSF and brain tissue microdialysates from a case series of 7 patients with progressive MS; and (3) in CSF at baseline and 60 weeks after natalizumab treatment in a cohort study of 17 patients with progressive MS. Correlation to neurofilament light, a marker of neuroaxonal injury, was tested. The effect of LCN2 on myelination and neurodegeneration was studied in a rat in vitro neuroglial cell coculture model. RESULTS: Intrathecal production of LCN2 was increased predominantly in patients with progressive MS (p < 0.005 vs relapsing-remitting MS) and displayed a positive correlation to neurofilament light (p = 0.005). Levels of LCN2 in brain microdialysates were severalfold higher than in the CSF, suggesting local production in progressive MS. Treatment with natalizumab in progressive MS reduced LCN2 levels an average of 13% (p < 0.0001). LCN2 was found to inhibit remyelination in a dose-dependent manner in vitro. CONCLUSIONS: LCN2 production is predominantly increased in progressive MS. Although this moderate increase does not support the use of LCN2 as a biomarker, the correlation to neurofilament light and the inhibitory effect on remyelination suggest that LCN2 might contribute to neurodegeneration through myelination-dependent pathways.